(untitled) (International Journal of Built Environment and Sustainability, 2025)
The construction of age-friendly cities has emerged as a social development objective in response to the growing senior population. Outdoor activities can enhance the elderly’s physical and psychological health, and an attractive outdoor setting can draw them in and encourage them to participate in more frequent and higher-quality outdoor activities. Nevertheless, research on the social and environmental traits of Chinese seniors in outdoor settings still needs to be done. To properly develop outdoor spaces in urban community parks, this study aims to investigate the outdoor activity preferences of senior citizens. Labor Square in Qingdao, China, was chosen as the research site because of its outdoor setting, and data were collected through the "System for Observing Play and Recreation in Communities" (SOPARC) to analyse the number and characteristics of age-friendly cities where older people live in different periods and different environmental areas. The findings indicate that older adults in Qingdao Labor Square love playing cards and square dancing. These two activities had the most significant number of participants during the survey. In addition, an excellent biological environment (more shrubs, shade trees, and pergolas with climbers) can encourage senior citizens to use the outdoors during the day, while open spaces are more alluring in the evening. This article investigates the outdoor activities that older people choose, as well as the characteristics of residential outdoor environments which offer a foundation for enhancing both the outdoor environment and senior health. These serve as a resource for designers.